B cell maturation antigen (BCMA) is dispensable for the survival of long-lived plasma cells - Menzel, Shannon; Roth, Edith; Wittner, Jens; Brey, Stefanie; Weckwerth, Leonie; Thomas, Jana; Winkler, Thomas H.; Schuh, Wolfgang; Jäck, Hans-Martin; Pracht, Katharina; Schulz, Sebastian (Nature Communications, 2025)
The survival of antibody-secreting plasma cells is essential for long-lasting humoral immunity. BCMA is proposed to promote APRIL-mediated survival signals. However, extensive shedding of murine BCMA raises doubts about its role as a signaling receptor. To unequivocally establish BCMA’s function in plasma cell survival, we generate two BCMA-deficient mouse lines and examine antigen-specific plasma cells post-immunization. Contrary to previous reports, both BCMA-deficient mouse lines have comparable numbers of antigen-specific long-lived plasma cells following both protein and mRNA immunizations. Transcriptome analysis reveals no reduction in survival signaling upon BCMA deletion. Interestingly, BCMA-deficient mice show increased total plasma cell numbers in the bone marrow and mesenteric lymph nodes after boost immunizations. These results indicate that BCMA has no intrinsic role in maintaining long-lived plasma cells. Instead, we propose that BCMA’s function is limited to acting as a soluble decoy receptor for APRIL, thereby fine-tuning the plasma cell population size by limiting survival factor availability. Our findings thus provide a strong argument against the APRIL-BCMA axis being a central mechanism for plasma cell longevity.
CRIS-Team Scopus Importer:2025-08-15

GLUT1-mediated glucose import in B cells is critical for anaplerotic balance and humoral immunity - Bierling, Theresa; Gumann, Amelie; Ottmann, Shannon; Schulz, Sebastian; Weckwerth, Leonie; Thomas, Jana; Geßner, Arne; Wichert, Magdalena; Kuwert, Frederic; Rost, Franziska; Hauke, Manuela; Freudenreich, Tatjana; et al. (Cell Reports, 2024)
Glucose uptake increases during B cell activation and antibody-secreting cell (ASC) differentiation, but conflicting findings prevent a clear metabolic profile at different stages of B cell activation. Deletion of the glucose transporter type 1 (GLUT1) gene in mature B cells (GLUT1-cKO) results in normal B cell development, but it reduces germinal center B cells and ASCs. GLUT1-cKO mice show decreased antigen-specific antibody titers after vaccination. In vitro, GLUT1-deficient B cells show impaired activation, whereas established plasmablasts abolish glycolysis, relying on mitochondrial activity and fatty acids. Transcriptomics and metabolomics reveal an altered anaplerotic balance in GLUT1-deficient ASCs. Despite attempts to compensate for glucose deprivation by increasing mitochondrial mass and gene expression associated with glycolysis, the tricarboxylic acid cycle, and hexosamine synthesis, GLUT1-deficient ASCs lack the metabolites for energy production and mitochondrial respiration, limiting protein synthesis. We identify GLUT1 as a critical metabolic player defining the germinal center response and humoral immunity.
CRIS-Team Scopus Importer:2024-02-23
Keywords: adaptive immune response; antibody-secreting cell; CP: Immunology; CP: Metabolism; glucose transporter type 1; GLUT1; glycolysis; metabolism; mitochondrial respiration; plasma cell; plasmablast

Identification of TFG- and Autophagy-Regulated Proteins and Glycerophospholipids in B Cells - Steinmetz, Tobit; Thomas, Jana; Reimann, Lena; Himmelreich, Ann-Kathrin; Schulz, Sebastian; Golombek, Florian; Castiglione, Kathrin; Jäck, Hans-Martin; Brodesser, Susanne; Warscheid, Bettina; Mielenz, Dirk (Journal of Proteome Research, 2024)
Keywords: metabolism; lysosome; JCHAIN; immunoglobulin; TRK-fused gene; ribosome; plasma cell; phosphatidylglycerol; autophagy; BCL10; endoplasmic reticulum stress; autophagy flux; B cell

Metabolic profiling of single cells by exploiting NADH and FAD fluorescence via flow cytometry - Abir, Ariful Haque; Weckwerth, Leonie; Wilhelm, Artur; Thomas, Jana; Reichardt, Clara; Munoz, Luis Enrique; Völkl, Simon; Appelt, Uwe; Mroz, Markus; Niesner, Raluca; Hauser, Anja; Fischer, Rebecca Sophie; et al. (Molecular Metabolism, 2024)
Objective: The metabolism of different cells within the same microenvironment can differ and dictate physiological or pathological adaptions. Current single-cell analysis methods of metabolism are not label-free. Methods: The study introduces a label-free, live-cell analysis method assessing endogenous fluorescence of NAD(P)H and FAD in surface-stained cells by flow cytometry. Results: OxPhos inhibition, mitochondrial uncoupling, glucose exposure, genetic inactivation of glucose uptake and mitochondrial respiration alter the optical redox ratios of FAD and NAD(P)H as measured by flow cytometry. Those alterations correlate strongly with measurements obtained by extracellular flux analysis. Consequently, metabolically distinct live B-cell populations can be resolved, showing that human memory B-cells from peripheral blood exhibit a higher glycolytic flexibility than naïve B cells. Moreover, the comparison of blood-derived B- and T-lymphocytes from healthy donors and rheumatoid arthritis patients unleashes rheumatoid arthritis-associated metabolic traits in human naïve and memory B-lymphocytes. Conclusions: Taken together, these data show that the optical redox ratio can depict metabolic differences in distinct cell populations by flow cytometry.
CRIS-Team Scopus Importer:2024-07-19
Keywords: FAD; Flow cytometry; Fluorescence; Metabolism; NADH; Real-time

Mitochondrial respiration in B lymphocytes is essential for humoral immunity by controlling the flux of the TCA cycle - Urbanczyk, Sophia; Baris, Olivier R.; Hofmann, Jörg; Taudte, Verena; Guegen, Naïg; Golombek, Florian; Castiglione, Kathrin; Meng, Xianyi; Bozec, Aline; Thomas, Jana; Weckwerth, Leonie; Mougiakakos, Dimitrios; et al. (Cell Reports, 2022)
To elucidate the function of oxidative phosphorylation (OxPhos) during B cell differentiation, we employ CD23Cre-driven expression of the dominant-negative K320E mutant of the mitochondrial helicase Twinkle (DNT). DNT-expression depletes mitochondrial DNA during B cell maturation, reduces the abundance of respiratory chain protein subunits encoded by mitochondrial DNA, and, consequently, respiratory chain super-complexes in activated B cells. Whereas B cell development in DNT mice is normal, B cell proliferation, germinal centers, class switch to IgG, plasma cell maturation, and T cell-dependent as well as T cell-independent humoral immunity are diminished. DNT expression dampens OxPhos but increases glycolysis in lipopolysaccharide and B cell receptor-activated cells. Lipopolysaccharide-activated DNT-B cells exhibit altered metabolites of glycolysis, the pentose phosphate pathway, and the tricarboxylic acid cycle and a lower amount of phosphatidic acid. Consequently, mTORC1 activity and BLIMP1 induction are curtailed, whereas HIF1α is stabilized. Hence, mitochondrial DNA controls the metabolism of activated B cells via OxPhos to foster humoral immunity.
CRIS-Team Scopus Importer:2022-06-17
Keywords: B lymphocyte; class switch recombination; CP: Immunology; germinal center; HIF1; hypoxia inducible factor 1; mammalian target of Rapamycin; mitochondrial DNA; mitochondrial respiration; mTOR; oxidative phosphorylation; phosphatidic acid; plasma cell; TCA cycle

Regulation of plasma cell homeostasis and antibody secretion through modulation of autophagy and endoplasmic reticulum stress by Trk-fused-gene (TFG) - Thomas, Jana; Steinmetz, Tobit; Mielenz, Dirk (EUROPEAN JOURNAL OF IMMUNOLOGY, 2022)
CRIS-Team WoS Importer:2023-01-27